11 DIABETIC FOOT CARE EDUCATION MATERIALS FOR PATIENTS IN WAHKIAKUM COUNTY, WASHINGTON. (1st January 2006) - Slade, I. R.
Abstract : Purpose: The number of patients with diabetic peripheral neuropathy is increasing in Wahkiakum County, Washington. Nationwide, estimates of the lifetime incidence of diabetic foot ulcers are as high as 25%, and as many as 30% of patients with ulcers eventually undergo amputation. With such morbidity and treatment costs in thousands of dollars per ulcer, prevention is important; patient education about foot self-care is part of this pursuit. A community medicine project was undertaken by the author in July 2005 to create clear, concise patient reference materials to help clinicians provide consistent education to all diabetics about the benefits of following a foot care plan. The materials target patients at Wahkiakum Family Practice Clinic (WFPC) in Cathlamet, Washington, the only medical clinic in Wahkiakum County. Methods: Current foot care recommendations were compiled from NIH, American Diabetes Association, and local care providers. Topics include routine diabetes management, daily foot inspection, skin and nail care, and footwear selection. The material was organized under subheadings that can be used to guide a clinician/patient discussion. There was agreement among local clinicians that the information was accurate and would be useful in patient education efforts. Results: The content was adapted to a brochure format for use at WFPC. The illustrations, level of detail, and simple language allow the brochure to stand alone, although it is intended to be initially reviewed during an office visit. A clinician may use this resource in providing individualized instruction relevant to each patient's risk of complications, level of understanding, and motivation for self-care activities. Conclusion: Printed reference materials may be useful in delivering consistent patient education. Providing this guidance is an important component of prevention endeavors.